2021
DOI: 10.1007/s10567-020-00333-1
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluations of Mental Health Programs for Children and Adolescents in the United States: A Systematic Review

Abstract: The United States (US) spent 201 billion dollars on mental health related concerns in 2016, ranking mental illness as the leading cause of disability and the single largest source of economic burden worldwide. With mental health related treatment costs and economic burden only projected to rise, there is an increasing need for cost-inclusive evaluations of mental health interventions in the US. This systematic review evaluated the intervention characteristics and the quality of 9 economic evaluation studies (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…A detailed description of the methods we used in our study (as well as other economic evaluation methods) can be found in Yates' (1996) manual. We also direct readers to Sung, Kacmarek, & Schleider (2021) for additional resources and recommendations for conducting economic evaluations for mental health interventions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A detailed description of the methods we used in our study (as well as other economic evaluation methods) can be found in Yates' (1996) manual. We also direct readers to Sung, Kacmarek, & Schleider (2021) for additional resources and recommendations for conducting economic evaluations for mental health interventions.…”
Section: Discussionmentioning
confidence: 99%
“…First, there is a great need for additional economic evaluations of interventions for youth. A recent systematic review found that there were only nine economic evaluations of youth mental health interventions, none of which were evaluations of digital interventions (Sung et al, 2021). Second, future research is needed to better understand for whom low-cost interventions are effective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mental disorders are projected to become the leading cause of mortality and morbidity by 2030 [ 6 ]. This growth is extremely problematic given that mental health disorders are the single largest contributing source of global economic burden [ 7 ]. This is evidenced by the global expenditure on treating depression and anxiety rising to US$ one trillion per year [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although there is a wide variety of evidence-based strategies that have been implemented to combat this growing issue, a reduction in the level of economic burden placed upon health systems and resources is yet to be experienced. In fact, the most discernible implementation barrier for mental health interventions is their often resource-intensive nature [ 7 ]. Not only does this place increased strain on health resource allocations, but it also makes treatment far less accessible for lower income families, as the cost often incurs out of pocket expenses [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%